Фінансова стійкість підприємства економічна сутність та особливості структури - Васильєв, Сергій В’ячеславович; Vasil`ev, Serhiy; Масляєва, Ольга Олександрівна; Masliaieva, Olga; Лапенко, Христина Олександрівна; Lapenko, Khrystyna (Чорноморський національний університетімені Петра Могили,ТОВ "ДКС Центр", 2024)
У статті проведено детальний аналіз поняття фінансових ресурсів підприємств. Визначено основну сутність фінансів підприємств як економічної категорії. Узагальнено різні наукові підходи до розуміння сутності фінансів підприємств і запропоновано їхнє уточнення. Розглянуто основні характеристики фінансів підприємств і їхню класифікацію. Представлено класифікацію фінансів підприємств, базуючись на дослідженнях вітчизняних та зарубіжних учених. Встановлено, що фінансові ресурси підприємства —це кошти, які є у його розпорядженні. Вони класифікуються за їхніми видами, складом та джерелами походження. Також розглянуто вплив фінансових ресурсів на загальний фінансовий стан підприємства. Проаналізовано, як різні джерела фінансування впливають на фінансову стійкість і платоспроможність підприємства. Визначено ключові фактори, що сприяють ефективному управлінню фінансовими ресурсами. Зроблено висновок, що комплексний підхід до управління фінансами забезпечує економічну ефективність і прибутковість підприємства. Дослідження підтвердило важливість детальної класифікації для ефективного управління фінансами підприємства. The article provides a detailed analysis of the concept of financial resources of enterprises. It defines the fundamental essence of enterprise finance as an economic category. Various scientific approaches to understanding the essence of enterprise finance are summarized, and clarifications are proposed. The main characteristics of enterprise finance and their classification are examined. The classification of enterprise finance is presented based on research by domestic and foreign scholars. It is established that financial resources of an enterprise are funds available at its disposal. They are classified according to their types, composition, and sources of origin. Additionally, the impact of financial resources on the overall financial condition of the enterprise is discussed. The effects of different sources of funding on the financial stability and solvency of the enterprise are analyzed. Key factors that contribute to effective financial resource management are identified. The conclusion is drawn that a comprehensive approach to financial management ensures economic efficiency and profitability of the enterprise. The research confirms the importance of detailed classification for effective financial management of the enterprise. Analyzing financial resources as an economic category is crucial for understanding their role in ensuring the stable operation of an enterprise. Studying financial resources helps identify key factors affecting the financial condition of a company, such as liquidity, solvency, and financial independence. Proper classification of financial resources enables effective management, optimizing their use across various areas of the enterprise's activities. Understanding the origins and impact of financial resources is essential for accurately identifying the sources and types of resources, which aids in making well-informed financial decisions. Evaluating the impact of different types of resources on the financial stability of the enterprise is also important, as it ensures the company's ability to meet financial obligations and handle unforeseen expenses. Analyzing the classification of financial resources reveals both the strengths and weaknesses of a company's financial strategy, as well as opportunities for improving financial management. It assists in developing effective financing plans that align with the company's short-term and long-term objectives. Classification of financial resources is crucial for maintaining an adequate level of liquidity, which allows the enterprise to sustain stable operations and adapt to market changes. It also aids in identifying the most effective sources of financing for investment projects and supporting expansion. Studying the classification of financial resources enables an assessment of the impact of the financial structure on the company's profitability and economic efficiency. This, in turn, enhances the company's competitiveness and helps achieve its strategic goals
Financial stability of an enterprise economic essence and structural features
Keywords: фінансовий стан підприємства; financial condition of the enterprise; фінансова стабільність; financial stability; фінансові ресурси; financial resources; ліквідність; liquidity; платоспроможність; solvency; фінансова незалежність; financial independence; економічна ефективність; economic efficiency; прибутковість підприємств; profitability of enterprises